Hubungan Antara Body Image Dengan Self Esteem Pada Wanita Dewasa Awal Pengguna Skincare - SAHRI, FIRDA NAROTAMA (2016)
THE RELATIONSHIP BETWEEN BODY IMAGE WITH SELF ESTEEM IN EARLY ADULT WOMEN OF SKINCARE USERS Firda Narotama Sahri firda.narotama@gmail.com Zahrotul Uyun Faculty of Psychology, University of Muhammadiyah Surakarta This study aims to determine the relationship between body image and self esteem in early adult women who use skincare, to determine the role of body image with self-esteem in early adult women who use skincare and to determine the level of body image and the level of self-esteem in early adult women who use skincare. Researchers used quantitative methods to achieve the objectives of this research. Subjects used in this study is a student at the Faculty of Economics and Business, University of Muhammadiyah Surakarta 18-22 years old who use skincare products. The results of the correlation coefficient (r) of 0.234 with p value = 0.008 < 0.01, which means there is a very significant positive relationship between body image with self esteem in early adult women of skincare users. Based on the results of analysis variables self esteem has the empirical mean (RE) of 74.71 and the mean hypothetical (RH) of 60 which means that self-esteem is the subject of research is high. Variable body image have the empirical mean (RE) of 81.51 and the mean hypothetical (RH) of 75 which means that self-esteem is being classified as research subjects. The effective contribution of 5.5% of body image to self esteem. Keywords: self-esteem, body image, early adult women, skincare